Perancangan Pembangkit Catu Daya Untuk Alat Pengukur pH Pada Limbah Cair Berbasis Solar Sel - Yoga Pratama; Nurhalim Nurhalim; Feranita Feranita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The use of electric power is one of the basic needs around the world, but there are some areas or places that are also not reached by electricity, such as in coal waste fields that require pH sensing to measure the quality standard of waste before disposal. The use of photovoltaic systems is an alternative to solve this problem. In this study, tests and measurements were carried out to determine the ability of the photovoltaic system as a power source for pH sensing. Measurement and testing on the prototype is carried out by applying varying loads and covering the surface of the solar panel which results in a change in the value of voltage and current. Based on the results of solar panel testing by covering the solar surface (shading), when the weather is clear with radiation of 812.4 W / m2 and a temperature of 33.7° C, the solar panels will stop filling the battery by closing 90% while in cloudy weather conditions with radiation of 242.4 W / m2 and a temperature of 31.9° C, solar panels will stop filling the battery by closing 40%. Keywords: photovoltaic, pH sensing, load variation, shading